2017
DOI: 10.1177/0194599817695545
|View full text |Cite
|
Sign up to set email alerts
|

HPV in Larynx Squamous Cell Carcinoma: New Serotypes and Survival Study within 10‐Year Follow‐up

Abstract: Objective To determine the presence of human papillomavirus (HPV) in head and neck squamous cell carcinoma, specifically in the larynx without the bias of other sublocations, and to describe the different serotypes of HPV and their impact on overall and disease-free survival after 10-year follow-up. Study Design Retrospective case series with chart review of ear, nose, and throat oncologic database. Setting Academic tertiary care hospital. Subjects A total of 123 samples of larynx squamous cell carcinoma were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 31 publications
1
12
1
Order By: Relevance
“…Another limitation of our study is the lack of formal voice quality assessment, which should be included in future prospective trials. Future studies should also incorporate human papillomavirus (HPV) testing, HPV has been implicated in laryngeal cancer oncogenesis, although its influence on prognosis remains unclear 50‐52 . Despite these limitations, this study represents one of the largest series reporting outcomes for patients with T2 glottic cancer in the modern era.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation of our study is the lack of formal voice quality assessment, which should be included in future prospective trials. Future studies should also incorporate human papillomavirus (HPV) testing, HPV has been implicated in laryngeal cancer oncogenesis, although its influence on prognosis remains unclear 50‐52 . Despite these limitations, this study represents one of the largest series reporting outcomes for patients with T2 glottic cancer in the modern era.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the study is also limited by the lack of formal assessment of voice quality after treatment. Another limitation is the lack of HPV status testing in our cohort given that recent data suggest that HPV status may have a prognostic impact in early stage laryngeal tumors …”
Section: Discussionmentioning
confidence: 99%
“…This study was conducted on specimens from our previous study, which examined whether HPV was identified in patients with laryngeal squamous cell carcinoma who were initially treated surgically for glottic cancer cell carcinoma. 11 Therefore, the inclusion criteria were g-SCCs from patients of both sexes who were initially treated with surgery only (ie, without chemotherapy or radiotherapy). In cases with subsequent recurrent or persistent disease, treatment consisted of salvage surgery, chemotherapy, and/or radiotherapy.…”
Section: Methodsmentioning
confidence: 99%